2014
DOI: 10.1002/adsc.201400766
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Redox Cascade for One‐Pot Synthesis of Uridine 5′‐Diphosphate Xylose from Uridine 5′‐Diphosphate Glucose

Abstract: Synthetic ways towards uridine 5′-diphosphate (UDP)-xylose are scarce and not well established, although this compound plays an important role in the glycobiology of various organisms and cell types. We show here how UDP-glucose 6-dehydrogenase (hUGDH) and UDP-xylose synthase 1 (hUXS) from Homo sapiens can be used for the efficient production of pure UDP-α-xylose from UDP-glucose. In a mimic of the natural biosynthetic route, UDP-glucose is converted to UDP-glucuronic acid by hUGDH, followed by subsequent form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…Further enzyme kinetic studies showed no inhibition by UDP‐GlcA and UDP (Figure S6, Supporting Information). Remarkably, inhibition data of human UGDH by the reduced by‐product NADH emphasize the need for an efficient cofactor regeneration of NAD + 23. In summary, these properties reveal His 6 UGDH as a favorable enzyme for the combination with other enzyme modules.…”
Section: Resultsmentioning
confidence: 95%
“…Further enzyme kinetic studies showed no inhibition by UDP‐GlcA and UDP (Figure S6, Supporting Information). Remarkably, inhibition data of human UGDH by the reduced by‐product NADH emphasize the need for an efficient cofactor regeneration of NAD + 23. In summary, these properties reveal His 6 UGDH as a favorable enzyme for the combination with other enzyme modules.…”
Section: Resultsmentioning
confidence: 95%
“…Most importantly, also at a high NAD + concentration being equimolar to UDP‐Glc NOX is necessary to maintain the NADH concentration below inhibitory concentrations (Supporting information, Fig. S8) . This is demonstrated by monitoring substrate and product concentrations during the course of reaction by MP‐CE (Supporting information, Fig.…”
Section: Resultsmentioning
confidence: 97%
“…In 2014, Nidetzky reported an in vitro one-pot synthesis of UDP-Xyl using UPD-Glc as a donor substrate via an oxidative decarboxylation process (Scheme 18). 48 A two-step conversion of UDP-Glc to UDP-Xyl via UDP-GlcUA was catalysed by UDP-glucose dehydrogenase (hUGDH) and UDP-xylose synthase (hUXS). hUGDH was coupled to a NAD + coenzyme regeneration cascade using a xylose reductase (CtXR) and bovine liver catalase.…”
Section: Scheme 17 A) Activated Aromatic Activated Glucopyranosides mentioning
confidence: 99%